Implementasi Komunikasi Dan Budaya Organisasi Terhadap Kinerja Karyawan Di Sekolah Insan Cendekia Madani Tangerang Selatan - Arief Permana Shidiq; Zaharuddin; Gada Sembada (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of communication and organizational culture on employee performance at the Insan Cendekia Madani School Office, South Tangerang. Specifically, the objectives are: (1) to examine the effect of communication on employee performance; (2) to examine the effect of organizational culture on employee performance; and (3) to examine the simultaneous effect of communication and organizational culture on employee performance. This research adopts a quantitative approach with a descriptive and associative research design. The population consists of employees at the Insan Cendekia Madani School Office, South Tangerang, with a sample of 83 respondents selected using Slovin’s formula. The results show that: (1) communication has a significant effect on employee performance, as indicated by a t-count value of 4.726, which exceeds the t-table value of 1.663; (2) organizational culture has a significant effect on employee performance, as shown by a t-count value of 73.536, which exceeds the t-table value of 1.663; and (3) communication and organizational culture simultaneously have a significant positive effect on employee performance, as demonstrated by an ANOVA test with an F-count of 21.631, exceeding the F-table value of 2.71 at a significance level of 0.000 (< 0.05). These findings suggest that strengthening internal communication and fostering a positive organizational culture contribute significantly to improving employee performance.